Penyuluhan Penggunaan Asap Cair dan Kemasan Vakum Pada UMKM Makanan Berbasis Hasil Laut di Tambaklorok, Semarang Utara - Meiliana Meiliana; Christiana Retnaningsih; Berta Bekti Retnawati (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2020)
Tambaklorok area in North Semarang has many Micro, Small, & Medium Enterprises (MSMEs) which produce seafood products, such as smoked fish, shrimp paste, fish or shrimp nugget, and fried anchovies. Most of the MSMEs in Tambaklorok still use traditional food technology for food processing and packaging, such as fish curing using smoke and simple packaging using plastic bags. The exposure of cooking smoke used for fish curing might impair the lung and respiratory system of the workers. Therefore, producers might utilize liquid smoke as an alternative smoked fish processing. Besides, in order to increase the production scale, producers might use vacuum packaging to extend the shelf life of food. The producers’ lack of knowledge regarding those processing and packaging alternatives might prevent the growth of their business ventures. For this reason, it is necessary to provide community outreach and counselling session to increase the knowledge and awareness of the producers on the processing and packaging alternatives. The participants welcomed such program and showed interests in applying those alternatives on their products.